Sugarcane vinasse: Environmental implications of its use - Christofoletti, Cintya Aparecida; Escher, Janaína Pedro; Correia, Jorge Evangelista; Marinho, Julia Fernanda Urbano; Fontanetti, Carmem Silvia (Elsevier, 2013)
The inadequate and indiscriminate disposal of sugarcane vinasse in soils and water bodies has received much attention since decades ago, due to environmental problems associated to this practice. Vinasse is the final by-product of the biomass distillation, mainly for the production of ethanol, from sugar crops (beet and sugarcane), starch crops (corn, wheat, rice, and cassava), or cellulosic material (harvesting crop residues, sugarcane bagasse, and wood). Because of the large quantities of vinasse produced, alternative treatments and uses have been developed, such as recycling of vinasse in fermentation, fertirrigation, concentration by evaporation, and yeast and energy production. This review was aimed at examining the available data on the subject as a contribution to update the information on sugarcane vinasse, from its characteristics and chemical composition to alternatives uses in Brazil: fertirrigation, concentration by evaporation, energy production; the effects on soil physical, chemical and biological properties; its influence on seed germination, its use as biostimulant and environmental contaminant. The low pH, electric conductivity, and chemical elements present in sugarcane vinasse may cause changes in the chemical and physical-chemical properties of soils, rivers, and lakes with frequent discharges over a long period of time, and also have adverse effects on agricultural soils and biota in general. Thus, new studies and green methods need to be developed aiming at sugarcane vinasse recycling and disposal. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Agroindustrial residue; Distillery effluent; Genotoxicity; Toxicity